Breath holding duration as a measure of distress tolerance: examining its relation to measures of executive control - Sütterlin, Stefan; Schroijen, Mathias; Constantinou, Elena; Smets, Elyn; Van den Bergh, Omer; Van Diest, Ilse (Frontiers in Psychology, 2013)
Recent research considers distress (in)tolerance as an essential component in the development of various forms of psychopathology. A behavioral task frequently used to assess distress tolerance is the breath holding task. Although breath holding time (BHT) has been associated with behavioral outcomes related to inhibitory control (e.g., smoking cessation), the relationship among breath holding and direct measures of executive control has not yet been thoroughly examined. The present study aims to assess (a) the BHT-task's test-retest reliability in a 1-year follow-up and (b) the relationship between a series of executive function tasks and breath holding duration. One hundred and thirteen students completed an initial BHT assessment, 58 of which also completed a series of executive function tasks [the Wisconsin Card Sorting Test (WCST), the Parametric Go/No-Go task and the N-back memory updating task]. A subsample of these students (N = 34) repeated the breath holding task in a second session 1 year later. Test-retest reliability of the BHT-task over a 1-year period was high (r = 0.67, p < 0.001), but none of the executive function tasks was significantly associated with BHT. The rather moderate levels of unpleasantness induced by breath holding in our sample may suggest that other processes (physiological, motivational) besides distress tolerance influence BHT. Overall, the current findings do not support the assumption of active inhibitory control in the BHT-task in a healthy sample. Our findings suggest that individual differences (e.g., in interoceptive or anxiety sensitivity) should be taken into account when examining the validity of BHT as a measure of distress tolerance.